Peran Brand Image: Pengaruh Celebrity Endorsement, E-WOM, dan Perceived Quality terhadap Purchase Intention Skincare pada Gen-Z - Fahlevi, Renza; Helen, Helen; Sinambela, Fitriana Aidnilla (DIALEKTIKA: Jurnal Ekonomi dan Ilmu Sosial, 2024)
This study aims to explore the impacts of Celebrity Endorsement in terms of Attractiveness, Trustworthiness, and Expertise, E-WOM, and Perceived Quality on Purchase Intention of local skincare products among Gen Z consumers, with Brand Image as a mediator. The research adopts a quantitative approach and explanatory method. Samples are selected using purposive technique within non-probabilistic methods. Data are collected through questionnaire surveys, with a total of 300 respondents. The gathered data will be analyzed using SmartPLS and SPSS. The findings reveal that E-WOM and the credibility of celebrity endorsements significantly impact the local skincare brand image among Gen Z. Perceived quality and brand image also play a significant role in enhancing purchase intention. Furthermore, it is found that brand image acts as a mediator in the relationship between E-WOM and celebrity endorsement, ultimately enhancing purchase intention of local skincare among Gen Z consumers.